2020
DOI: 10.3389/fgene.2020.593577
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Class III Peroxidase Gene Family in Potato (Solanum tuberosum L.)

Abstract: Class III peroxidases (PRXs) are plant-specific enzymes and play important roles in plant growth, development and stress response. In this study, a total of 102 non-redundant PRX gene members (StPRXs) were identified in potato (Solanum tuberosum L.). They were divided into 9 subfamilies based on phylogenetic analysis. The members of each subfamily were found to contain similar organizations of the exon/intron structures and protein motifs. The StPRX genes were not equally distributed among chromosomes. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The class III peroxidase gene family (PRXs) is a widely distributed isozyme family type that is well known to have various short names, e.g., PRX, POD, POX, and PER, and contributes to multiple significant physiological reactions in plants [ 1 ]. Its key functions are involved in causing reduction–oxidation reactions in electrons triggered by H 2 O 2 and other types of organic and inorganic compounds, e.g., eliminating the excess amount of H 2 O 2 produced in plant tissue, facilitating wound healing, cross-linking small molecules of oxidized poly-lignin within the cell wall, and providing protection against destructive insects and pathogens [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The class III peroxidase gene family (PRXs) is a widely distributed isozyme family type that is well known to have various short names, e.g., PRX, POD, POX, and PER, and contributes to multiple significant physiological reactions in plants [ 1 ]. Its key functions are involved in causing reduction–oxidation reactions in electrons triggered by H 2 O 2 and other types of organic and inorganic compounds, e.g., eliminating the excess amount of H 2 O 2 produced in plant tissue, facilitating wound healing, cross-linking small molecules of oxidized poly-lignin within the cell wall, and providing protection against destructive insects and pathogens [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have revealed that different types of plants contain a large number of PRXs with different contributions, e.g., 73 PRX genes in Arabidopsis [ 5 ], 138 PRX genes in rice [ 6 ], 119 PRX genes in maize [ 7 ], 94 PRX genes in pear [ 8 ], 91 POD genes in cassava [ 9 ], 102 PRX genes in potato [ 1 ], and 90 POD genes in birch [ 10 ], among others. The proteins formed by these genes exhibit highly conserved amino acid motifs that include two conserved histidine motifs with chemical binding sites for heme, distal histidine vital for catalytic activity, and eight cysteines that interact to form constant disulfide bonds and are essential amino acids in the secondary structure of peroxidases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the GO enrichment revealed a functional bias of TDGs across the four potato genotypes ( Figure 4B ). This is supported by recent studies of specific gene families in potato ( Herath and Verchot, 2020 ; Liu et al, 2020 ; Yang et al, 2020 ; Xuanyuan et al, 2022 ) and provided an important source for genetic diversity in plants for adaptive evolution against various environmental stimuli. These results are similar to a previous study conducted on two maize genotypes (such as B73 and PH207) where more than 49% of B73’s and 40% of PH207’s TDGs were lineage-specific ( Kono et al, 2018 ).…”
Section: Discussionmentioning
confidence: 78%
“…From the sesame pan-genome gene sets, 83, 82, 60, 59, 54, and 54 peroxidase genes were counted in Zongzhi13, Swetha, Mishuozima, Baizhima, Goenbaek, and Yuzhi11 genomes, respectively ( Figure 2 ). Similarly to the peroxidase count variability observed at the intra-species level in sesame, high inter-species variability was observed with 138, 119, 102, 90, 73, and 47 peroxidase genes counted in Oryza sativa [ 76 ], Zea mays [ 77 ], Solanum tuberosum [ 78 ], Betula pendula [ 79 ], A. thaliana [ 80 ], and Vitis vinifera [ 81 ], respectively. Most of the gene clusters (25) were shared by all varieties while only Swetha exhibited species-specific gene clusters (7).…”
Section: Resultsmentioning
confidence: 83%